Applications and Extensions of Fourier Ptychography. (November 2022) - Aidukas, Tomas; Wechsler, Felix; Loetgering, Lars; Zhou, Kevin; Horstmeyer, Roarke
Abstract : Abstract: This is the third article within a three-part series on Fourier ptychography, which is a computational microscopy technique for high-resolution, large field-of-view imaging. While the previous articles introduced the working principles of the technique, in this article we focus on the practical benefits that it brings to the imaging community. We present a didactic overview of the most important and well-established practical use-cases such as gigapixel imaging, quantitative phase contrast, thick sample imaging, and aberration metrology. We also discuss how Fourier ptychography can leave the visible light domain and venture into the realm of smaller wavelengths such as X-rays and electrons, among other topics.